Is biofeedback an effective treatment for tension headaches in adults?. Issue 9 (September 2015) - Jethwa, Krunal; Tyler, Carl
Abstract : Evidence‐Based Answer : The answer is unclear (No SOR given, disputed metaanalysis and conflicting RCTs).